Economic Burden and Health-Related Quality of Life of Respiratory Syncytial Virus and Influenza Infection in European Community-Dwelling Older Adults. (31st March 2022) - Mao, Zhuxin; Li, Xiao; Korsten, Koos; Bont, Louis; Butler, Christopher; Wildenbeest, Joanne; Coenen, Samuel; Hens, Niel; Bilcke, Joke; Beutels, Philippe; ,
Abstract: Background: Respiratory syncytial virus (RSV) and influenza virus infections result in a considerable mortality and morbidity among the aging population globally. Influenza vaccination for older adults before the seasonal influenza epidemic has been evaluated to be cost-effective in many countries. Interventions against RSV in older adults are in the pipeline, and evaluating their cost-effectiveness is crucial for decision making. To inform such evaluations, our aim was to estimate average costs and health-related quality of life (HRQoL) in older adults with RSV and influenza infection. Methods: The European RESCEU observational cohort study followed 1040 relatively healthy community-dwelling older adults aged 60 years and older during 2 consecutive winter seasons. Health care resource use and HRQoL were collected and analyzed during RSV episodes, and also during influenza episodes. Country-specific unit cost data were mainly obtained from national databases. Direct costs were estimated from a patient, health care provider, and health care payers' perspective, whereas indirect costs were estimated from a societal perspective. Due to small sample size, no formal statistical comparisons were made. Results: Thirty-six RSV and 60 influenza episodes were reported, including 1 hospitalization. Means (median; first-third quartile) of €26.4 (€5.5; 0–47.3) direct and €4.4 (€0; 0–0) indirect costs were reported per nonhospitalized RSV episode, and €42.5 (€36; 3.3–66.7) direct and €32.1 (€0; 0–0) indirect costs per nonhospitalized influenza episode. For RSV episodes, the utility value decreased from 0.896 (0.928; 0.854–0.953) to 0.801 (0.854; 0.712–0.937) from preseason to 1 week after symptom onset; for influenza, the change was from 0.872 (0.895; 0.828–0.953) to 0.664 (0.686; 0.574–0.797). Conclusions: The average costs and HRQoL estimates of older adults treated outside the hospital can be used to inform the design of future studies and the decision making regarding interventions to prevent RSV infection in older adults. Larger studies are needed to provide better country-specific and complementary cost estimates and to allow for formal statistical comparison of costs between RSV and influenza. Clinical Trials Registration: NCT03621930.